Producing protest news: Representations of contentious collective actions in mainstream print media - Spyridou, Lia Paschalia (My University, 2015)
© 2015, University of Nicosia. All rights reserved. When covering protests, evidence suggests that the media tend to resort to the ‘protest paradigm’, a routinized template to produce protest stories, downsizing the scope, claims and mobilisation effects of the protest movements. This article examines the representations of protests by Cypriot mainstream media on the occasion of the recent economic remedies imposed by the EU/IMF. Framing analysis has indicated that media coverage adheres to the protest paradigm as the dominant frames of ‘drama’ and ‘inevitability’ signal an explicit effort to marginalise and delegitimise their claims, and therefore discredit their significance and potential to affect policy making. And yet, the findings suggest that the political orientation of the media does affect the representation of protests as the left-wing media provide empowering representations of the protests. Overall, however, media coverage is elite-sourced, episodic, lacking in-depth analysis and alternative policy suggestions. This study contributes to the protest paradigm thesis, and argues that recent evidence claiming a repair of the paradigm are counterbalanced in the case of protests that radically question the status quo. Finally, considering the moderate protest movement that developed in Cyprus, the findings are discussed in conjunction with specific traits of the Cypriot political culture providing some preliminary interpretation on how the politics of futility and fear coupled by the ‘responsible politics’ discourse articulated systematically in the media, can offer a degree of insight into the development of modest protest dynamics.
Keywords: Framing; News reporting; Protest dynamics; Protest movements; Protest paradigm; Representation; Responsible politics